Barriers to male-partner participation in programs to prevent mother-to-child HIV transmission in South Africa. - Koo, Kevin; Makin, Jennifer D; Forsyth, Brian W C (AIDS education and prevention : official publication of the International Society for AIDS Education, 2013)
Efforts to prevent mother-to-child HIV transmission (PMTCT) in sub-Saharan Africa have focused overwhelmingly on women, to the unintended exclusion of their male partners. A cross-sectional study was conducted in Tshwane, South Africa, to determine barriers to male-partner participation during PMTCT. In-depth interviews were conducted with 124 men whose partners had recently been pregnant, and five focus group discussions were held with physicians, nurses, HIV counselors, and community representatives. Qualitative analysis revealed that while most fathers believed that HIV testing is an important part of preparing for fatherhood, there are formidable structural and psychosocial barriers: the perception of clinics as not "male-friendly," a narrow focus on HIV testing instead of general wellness, and a lack of expectations and opportunities for fathers to participate in health care. Coupled with more family-oriented approaches to PMTCT, measurable improvements in the way that male partners are invited to and engaged in HIV prevention during pregnancy can help PMTCT programs to achieve their full potential.
Keywords: Adult; Attitude to Health; Counseling; Cross-Sectional Studies; Fathers; Female; Focus Groups; HIV Infections; Humans; Infant, Newborn; Infectious Disease Transmission, Vertical; Interviews as Topic; Male; Middle Aged; Mothers; Patient Acceptance of Health Care; Pregnancy; Qualitative Research; Sexual Partners; Socioeconomic Factors; South Africa; Voluntary Programs